Antagonistic Effect of Dichloromethane on Oreochromis mossambicus and Immune Stimulation Activity of Aloe Vera - Nirmala, G. N.; Sharma, Akshata; Ragunathan, Venkataraghavan (Frontiers in Environmental Science, 2022)
The aim of the research work is to study the aquatic toxicity of the dichloromethane (DCM) in a Oreochromis mossambicus along with the aquatic toxicity studies an Insilico research work was also done to improve the immune system of the fish, which would help to fight against the oxidative stress and neurotoxic effect of dichloromethane. The activities of glutathione-S-transferase and acetylcholinesterase enzymes were studied from the brain, muscle, liver, and gills of the fish treated with different concentrations of dichloromethane that is 730ppm, 760ppm and 790ppm. The histopathological and haematological studies were also done at various concentration of dichloromethane. The molecular docking studies of the bioactive compounds of Aloe vera against interleukin-1β was done and the drug properties were also analysed. The lethal concentration LC50 of the fish was found to be 760 ppm. The haematological study reveals that the tissues that was exposed to 760 ppm of DCM has an elevated count of leukocytes and high amount of haemoglobin, and the platelet count was very low. The liver histopathological study indicated the cellular alterations such as necrosis and the gills showed the lamellar fusion and congestion. The compounds such as sitosterol has shown good binding energy (-12.398Kcal/mol) followed by squalene of (-12.157Kcal/ mol) against the interleukin-1β. The pharmacokinetic properties were also analysed which has given satisfactory results. Thus, the haematological and histopathological studies reveal that the dichloromethane has a potential ability to induce oxidative stress and neurotoxic effects. Hence, the Phyto-chemicals of Aloe vera can improve the immune system to fight against the neurotoxicity of the dichloromethane which can be further validated by invitro and in vivo studies.